Assessment of the drinking water quality from natural sources in the Kharkiv city - A. A. Lisnyak; M. I. Kulyuk (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія, 2022)
Improving the reliability and quality of the population's drinking water supply is one of the primary social problems, since the health of the population largely depends on the level of safety of drinking water.